The dynamics of sociopolitical networks in the collective action of the Afro-descendant movement in the Americas - Antón Sánchez, Jhon Herlyn (2023)
This article analyzes the sociopolitical dynamics of the Afro-descendant social movement based on the structuring of interaction networks. We argue that sociopolitical networks have constituted the strategy for influencing and collective action of the social movement, especially in the transnational sphere. However, the lack of continuity in processes, limited funding, and dispersion generate a manifest weakness in achieving agendas. The variety of networks ranging from Afrocentric to institutional, as well as their left and right ideologies, are considerations that must be taken into account when promoting empowerment projects. Nevertheless, more attention should be given to Afrocentric networks, as they are more autonomous, independent, and enduring.